Effect of viscous soluble dietary fiber on glucose and lipid metabolism in patients with type 2 diabetes mellitus: a systematic review and meta-analysis on randomized clinical trials - Lu, Kun; Yu, Tingqing; Cao, Xinyi; Xia, Hui; Wang, Shaokang; Sun, Guiju; Chen, Liang; Liao, Wang (Frontiers in Nutrition, 2023)
(1) Background: The effect of viscous soluble dietary fiber on glucose and lipid metabolism in type 2 diabetes mellitus (T2DM) remains controversial, and the dose-response relationship of its effect on blood glucose and blood lipid level is still unclear; (2) Methods: We conducted comprehensive searches in several databases up to January 17, 2023, a dose-response analysis of randomized controlled trials (RCTs) was conducted to investigate the effect of viscous dietary fiber on glucose and lipid metabolism in patients with T2DM; (3) Results: Statistical significance are observed in the decreases of glycosylated hemoglobin (HbA1c) (mean difference) (MD = -0.47; 95%CI: (-0.66, -0.27), fasting blood-glucose (FBG) (MD = -0.93; 95%CI: (-1.46, -0.41), total cholesterol (TC) (MD = -0.33; 95%CI: (-0.46, -0.21), and low-density lipoprotein and cholesterol (LDL-C) (MD = -0.24; 95%CI: (-0.35, -0.13). On the contrary, no difference was observed regarding the level of high-density lipoprotein cholesterol (HDL-C) or triglyceride (TG). In addition, the effect on fasting insulin remains unclear. Results from the subgroup analyses showed that the effect of the intervention duration longer than 6 weeks had a significant effect on the level of HbA1c; the treatment dosage higher than 8.3g/day affected significantly on the level of FBG; (4) Conclusions: Supplementation of viscous dietary fiber is beneficial to control blood glucose and blood lipid in T2DM.